Genetic and Heritability Estimation of Water Apple (Syzygium aqueum (Burm.f.) Alston) - Nasution, Fitriana; Hadiati, Sri (Yayasan Pertanian Tropika Indonesia (YPTI), 2019)
Nine different accessions of water apples were evaluated at Indonesian Tropical Fruit Research Institute(ITFRI), Solok, West Sumatera from January 2013 to December 2014. This present study was aimed to evaluate the variability, heritability, genetic advance and its characters in nine different accessions to provide useful information in the improvement program of water apples. The research used Randomized Complete Block Design (RCBD) with two replications. The ANOVA results exposed significant differences at 5% probability level for all characters. Genotypic variance on fruit weight, fruit length, fruit diameter, leaf length were broad. However, the genotypic variance on total soluble solids, leaf width were narrow. The phenotypic variation for all characters was broad. The heritability estimation was categorized as low, moderate, and high. High heritability estimation was recorded for fruit weight, fruit length, fruit diameter, and leaf diameter. Moderate heritability estimation was noticed for total soluble solids. Leaf width had low heritability estimation. High heritability and high genetic advance were observed on fruit weight.